Fertile Seedbed for Planting Habaib’s Religious Political Authority - Santosa, Nyong Eka Teguh Iman; Reyaz, Mohammad (Religió Jurnal Studi Agama-agama, 2023)
The Ḥaḍramī people in Indonesia, popularly called ḥabā’ib, are those of Arab descent who have contributed to the history of this nation. Their same origin does not necessarily make this community homogeneous, especially when it comes to Islam and Indonesianness. The vibrant tones that characterize this diversity can even be traced back to the colonial era. One of them is related to the struggle for the influence of h}abā’ib’s religious politics in the public sphere. The recent growth of their authority at the national level has drawn attention and prompted a key inquiry about what infrastructure and superstructure are conducive and supportive for this to occur. A heuristic analysis is conducted to explore the issue. This study reveals that ḥabā’ib’s religious politics have grown in prominence in Indonesia because they have hospitable spaces to grow in accord with the construction of their identity as a social and religious elite group. Meanwhile, this phenomenon is difficult to develop in cultural settings that do not accommodate the expressions of supremacy based on race, ethnicity, or ancestry. The existence of cultural spaces with different inclinations in addressing h}abā’ib’s identity is still constitutionally permitted in Indonesia. Muslims have the wisdom as well as the resilience to manage the struggle for religious and political authority in their respective Islamic cultural environments. The state and government must continue to position themselves as the large tent for the diversity of their people.